Static and dynamic performances of lubricated contacts with Maxwell fluids : a mixed model - Bou-Saïd, Benyebka; Najji, Brahim (European Journal of Computational Mechanics, 2005)
The influence of non Newtonian effects on the static and dynamic performance of slider and journal bearings in thermohydrodynamic regime is analyzed using a mixed model with an integral formulation and a Finite Element method resolution. The mixed model is used here for the first time in lubrication. It takes into account the implicit rheological laws. The shear stress field appears in this formulation as a nodal unknown and eases the use of rheological laws with yield criteria. This mixed model can accept various constitutive laws of Maxwell type (linear or non-linear viscous, viscoelastic or viscoelastic plastic). Corresponding energy equations are also developed. Results show that when compared to the classical viscous solution, viscoelastic effects: – significantly modify friction torque when operating under steady state conditions, – improve bearing dynamic coefficients but can, under specific running conditions, increase the instability zone.